4(c+2)+10=2c-6

Simple and best practice solution for 4(c+2)+10=2c-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(c+2)+10=2c-6 equation:


Simplifying
4(c + 2) + 10 = 2c + -6

Reorder the terms:
4(2 + c) + 10 = 2c + -6
(2 * 4 + c * 4) + 10 = 2c + -6
(8 + 4c) + 10 = 2c + -6

Reorder the terms:
8 + 10 + 4c = 2c + -6

Combine like terms: 8 + 10 = 18
18 + 4c = 2c + -6

Reorder the terms:
18 + 4c = -6 + 2c

Solving
18 + 4c = -6 + 2c

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-2c' to each side of the equation.
18 + 4c + -2c = -6 + 2c + -2c

Combine like terms: 4c + -2c = 2c
18 + 2c = -6 + 2c + -2c

Combine like terms: 2c + -2c = 0
18 + 2c = -6 + 0
18 + 2c = -6

Add '-18' to each side of the equation.
18 + -18 + 2c = -6 + -18

Combine like terms: 18 + -18 = 0
0 + 2c = -6 + -18
2c = -6 + -18

Combine like terms: -6 + -18 = -24
2c = -24

Divide each side by '2'.
c = -12

Simplifying
c = -12

See similar equations:

| 13n=5 | | (-11m)-2m= | | 27=90+c | | -2x-77=-11x+40 | | 3x=108solver | | 12w-6w-3w=12 | | 10x-73=71 | | 3(v-6)-8=-7(-2v+4)-3v | | 24=96n | | 15x-27=42-8x | | -81=3x | | 2(x-1)+3(2x-1)=7 | | a+(b+12)= | | 12-d=5 | | 2x*x=92 | | 2(21.5-2.5y)+5y=43 | | 336/540 | | -3x^2=-4+8 | | 5j-4j=16 | | 2x/-2=-6/-2 | | 8x/5y=6 | | 3j^2+18j-48=0 | | 2(21.5+5y)+5y=43 | | 5/8m/25 | | 2x-(8x+5)=7x-31 | | sin(2x)=9.44 | | N-3/10=3/5 | | 36=k*12 | | 5/8m*25 | | 7y=33+5x | | 3u-u+3=11 | | -[10z(20z+7)]=7+(9z+8) |

Equations solver categories